(untitled) (Journal of the College of Education for Women, 2021)
The present work focuses on examining the strategy of cognitive trips and the Arabic language teachers’ training needs of such a strategy when teaching Arabic language courses in the Saudi Arabia Kingdom. To achieve the objective of the study, and check whether this strategy is used in lesson planning, lesson teaching, or lesson assessment, a descriptive approach and a questionnaire have been adopted. The researchers used a number of statistical tools, and chose a purposive sample, which consists of (58) Arabic language teachers from Saudi Arabia Kingdom. Results have shown that the training needs of Arabic language teachers for implemining the strategy of cognitive journeys while teaching Arabic language courses came in the following order: the area of lesson planning with 63.8%, lesson implementation with 60.3%, and then evaluating the lesson with 56.9%. Besides, the strategy of cognitive trips that has been applied on learners needs to be used virtually, and to maintain its origins. Finally, the researchers have recommended identifying the strategy of knowledge trips and employing it in the educational process. The researchers have further suggested to provide laboratories equipped with smart devices and the Internet, and to encourage teachers to have intensive training to master the strategy of knowledge trips, and adopt it as an effective method of teaching. They have further suggested to arrange training courses all over the kingdom to improve teacher’ educational results.